AMELIORATION IN APPROACHES FOR ENHANCED PULMONARY DRUG DELIVERY - CHOUDHARY, SURAJ; PATIL, APARAJITA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Pulmonary disorders including asthma, chronic obstructive pulmonary disorder (COPD), cystic fibrosis, and other severe conditions like cancer have indeed made pulmonary drug delivery systems, both, an area of interest as well as concern. The mortality rate, around 8%, has enabled researchers to develop novel technologies for efficient drug delivery and reduced side effects. As the drug delivery through inhalation involves two major influencing factors, that is, formulation type and the device used for inhalation, various strategies have been designed with an intent to upgrade the existing drug formulations and devices used. Apart from this, various targeting strategies including gene therapy and magnetic targeting so as to improve the target specificity of the administered drug in the regions of the pulmonary system have been developed. In spite of these advancements, pulmonary drug delivery appears to be challenging in terms of formulation design and animal model design as well as lack of availability of FDA-approved excipients for inhalation. Persistent efforts have been made by the researchers in combining various strategies to negate the drawbacks/limitations of pulmonary drug delivery so as to develop a drug delivery system with improved efficacy and negligible adverse effects.